Levels and durability of neutralizing antibodies against SARS-CoV-2 Omicron and other variants after ChAdOx-1 or BNT162b2 booster in CoronaVac-primed elderly individuals. Issue 4 (April 2023) - Takheaw, Nuchjira; Liwsrisakun, Chalerm; Laopajon, Witida; Pata, Supansa; Chaiwong, Warawut; Inchai, Juthamas; Duangjit, Pilaiporn; Pothirat, Chaicharn; Bumroongkit, Chaiwat; Deesomchok, Athavudh; Theerakittikul, Theerakorn; Limsukon, Atikun; et al.
Abstract: The outbreak of the SARS-CoV-2 Omicron variant raised the need for vaccine boosting. We evaluated the efficiency of the third booster vaccine, ChAdOx-1 or BNT162b2, in causing a neutralizing antibody (NAb) response and its durability against the Omicron and other variants in elderly individuals previously vaccinated with 2-dose CoronaVac inactivated vaccine. After receiving 2-dose CoronaVac, only 2.2% of subjects had NAbs against the Omicron variant above the cut-off value. Four weeks after boosting, the number of subjects who had NAb levels above the cut-off values in the ChAdOx-1 and BNT162b2 vaccine boosting groups increased to 41.7% and 54.5%, respectively. However, after 12 and 24 weeks of boosting with any vaccines, NAb levels against the Omicron variant dramatically waned. Twenty-four weeks after boosting, only 2% had high levels of NAbs against the Omicron variant. Compared to other variants, the Omicron variant was less responsive to boosting vaccines. The waning rate of NAb levels for the Omicron variant was much faster than that observed in the Alpha, Beta and Delta variants. To combat the Omicron variant, the fourth booster dose is, therefore, recommended for elderly individuals.